Implementasi Kebijakan Bantuan Kesejahteraan Lanjut Usia Di Kecamatan Tanimbar Selatan Kabupaten Maluku Tenggara Barat - Rangkoly, Ivo; Rumapea, Patar; Dengo, Salmin (Sam Ratulangi University, 2014)
A case study on the implementation of welfare policies in the District senior South Tanimbar West Southeast Mollucas district. This study used qualitative methods. Data sources / informants were interviewed as many as 16 people consisting of 3 officers / employees of Department of Social Welfare and Labor. Head South Tanimbar. 3 village heads and 6 elderly people are not potential and the data collection process using interview techniques. The results show that the implementation of welfare policies in the District senior South Tanimbar. Southeast MoluccasÂ regency west wanted not run well there are some obstacles / barriers in the implementation process of budget constraints. lack of technical guidance. lack of facilities and infrastructure for implementing companion. and delays time. It can be concluded that the process of policy implementation assistance in the District senior South Tanimbar West Southeast Moluccas district has not been effective. So it can be suggested: (1) Local Government or the Department of Social Welfare who directly carry out the process of division in their local villages to prevent cuts or misappropriation of find and on target. (2) need additional find for infrastructure supplicants executive assistant in elderly aid policy implementation (3) the government should work just as well with the post offices so that the process is not delayed disbursements of time. (4) the government should provide special orphanage for the elderly who are not potential in channeling funds to a more focused and targeted in providing assistance. Keyword: policy implementation elderly welfare assistance.